Global research trends in therapeutic drug monitoring of antimicrobials from 2000 to 2023: a bibliometric analysis - Li, Hao; Jiang, Manxue; Kong, Lingti (Frontiers in Pharmacology, 2024)
Objective: The practice of therapeutic drug monitoring (TDM) is widely used for maximizing the clinical efficacy of antimicrobials. However, a systematic bibliometric analysis providing an overview of this field is lacking at present. The aim of the current study was to identify hotspots and trends in antimicrobial TDM, highlight collaborations and influences among countries, institutions, and journals, and assess the knowledge base for further development of clinical research.Research design and methods: Articles and reviews related to TDM of antimicrobials from the Web of Science Core Collection were collected. CiteSpace and VOSviewer, two visualization tools, were utilized to graphically assess the key elements within this domain, including mapping of countries and regions, institutions, keywords, and references associated with the field of antimicrobial TDM. Through this approach, we were able to successfully provide a comprehensive visual overview of the research landscape, highlighting the significant players and thematic trends in the literature. Results: From 2000 to 2023, a total of 17,236 authors from 4,112 institutions in 112 countries/regions published 3,710 papers in 819 academic journals. The United States had the highest number of publications, with University of Queensland identified as the most active institution. The journal with the greatest number of publications was Therapeutic Drug Monitoring, whereas Antimicrobial Agents and Chemotherapy was the most co-cited journal. Current research focuses on pharmacokinetics, pharmacodynamics, vancomycin, posaconazole, invasive fungal infection and critically ill patients. Promising hotspots for future research include vancomycin, voriconazole, meropenem, isavuconazole, posaconazole, and teicoplanin. Moreover, vancomycin and critically ill patients remain a hot topic of future research. Conclusions: Using bibliometric and visualization methods, the research hotspots of antimicrobial drugs in TDM were analyzed. The continued increase in the number of annual publications